TINJAUAN YURIDIS TERHADAP UPAYA KEBERATAN ATAS PUTUSAN BADAN PENYELESAIAN SENGKETA KONSUMEN KOTA MEDAN ANTARA DEDEK CAHYO MELAWAN PT EXPRESS LIMO NUSANTARA PADA PERKARA NOMOR 472/Pdt.G/2007/PN.Mdn. - Jeckon Franki Hutabarat; Rika Lestari; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Consumer protection is all the effort that ensure legal certainty to provide protection to consumers. In the current business development , consumer disputes can arise and require regulation that contains clear provision for any settlement of consumer disputes. Settlement of consumer dispute can be done outside the court as provided in Act No. 8 of 1999 on Consumer Protection. The research purpose is to conduct reviews legally of BPSK decision which is final anda binding, knpwing the process of filing an appeal against the decision BPSK anda absolute competence Medan District Court case number 474/Pdt.G/2007/PN,Mdn. This type of research used by the author in this research is normative juridicial research. The author in this study discusses the synchronization principle of law.The result obtained from the study consist three main issues, First: Decision BPSK said to be final and binding, if the dispute has been through yhe process of inspection pursuant to reach verdict in BPSK: Second : Filing an objection yo the case number 472/Pdt.G/2007/PN.Mdn not meet the requirements stipulated in article 6 paragraph (3) of the Regulation of the Supreme Court No. 1 of 2006 , so the reasons for filing objections has no legal basis in accordance with the existing provisions: Third: Medan District court in examining the objection only refers to Article 56 paragraph (2) of the Act Protection Consumer anda do not pay attention to the provisions of the arbitration so wrong in applying the law. Advice from the authir of the problems studied , First: that the decision BPSK can be directly executed and not given the effort to raise objections: Second: District Court can be reject the arbitration BPSK decision check: Third: Dostricy Court in order to apply the precautionary principle and through in checking objection to BPSK arbitration decision.Keywords: Mind-Decision-BPSK